Intropopulation variability of Rosa oxyodon Boiss. indications on Gunib plateau - B. A. Abakarova; Z. M. Asadulaev (Юг России: экология, развитие, 2015)
The data of intrapopulation variability of caucasian endemic Rosa oxyodon Boiss. are given in the article on the base of the complex of quantitative indications of the bush and biometric factors of the leaf.